Digital transformation in journalism and news media : media management, media convergence and globalization - Friedrichsen, Mike; Kamalipour, Yahya R. (Springer, 2017)
This book analyzes various digital transformation processes in journalism and news media. By investigating how these processes stimulate innovation, the authors identify new business and communication models, as well as digital strategies for a new environment of global information flows. The book will help journalists and practitioners working in news media to identify best practices and discover new types of information flows in a rapidly changing news media landscape.
Keywords: Online journalism.; Digital media.; Journalism -- Technological innovations.; elektronické knihy; electronic books